A Systematic Evidence Review of the Check-In/Check-Out Program for Reducing Student Challenging Behaviors. (October 2015) - Maggin, Daniel M.; Zurheide, Jamie; Pickett, Kayci C.; Baillie, Sara J.
Three-tiered models of prevention are increasingly being adopted by schools to address the behavioral needs of students. A critical component of multitiered systems are secondary interventions used with students in need of behavioral support but who are not candidates for individualized interventions. Despite the importance of secondary interventions, questions remain regarding which approaches have sufficient empirical support to warrant their use. The purpose of this review was, therefore, to examine the research underlying the Check-In/Check-Out (CICO) program, a widely used secondary intervention, to determine the strengths, limitations, and generality of the accumulated research. The What Works Clearinghouse (WWC) procedures for evaluating single-case and group-based research were applied with results indicating mixed support for the program. Specifically, there were a sufficient number of single-case research studies to deem the CICO program as evidence-based, while the group-based research had no demonstrated effects. These findings are discussed in terms of future research on the CICO program and the broader implications for selecting and implementing secondary interventions in school settings.